Бічний аміотрофічний склероз на тлі цукрового діабету - Юзвенко, Т. Ю. (Clinical Endocrinology and Endocrine Surgery, 2012)
The paper presents data on the epidemiology, pathogenesis and diagnostics of amyotrophic lateral sclerosis. A case of the disease in a patient with diabetes mellitus and diabetic polyneuropathy is shown.